2017
DOI: 10.1177/1941738117726070
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in Australian Rules Football: An Overview of Injury Rates, Patterns, and Mechanisms Across All Levels of Play

Abstract: Context:The nature of Australian rules football (Australian football) predisposes both unique and common injuries compared with those sustained in other football codes. The game involves a combination of tackling, kicking, high-speed running (more than other football codes), and jumping. Two decades of injury surveillance has identified common injuries at the professional level (Australian Football League [AFL]).Objective:To provide an overview of injuries in Australian rules football, including injury rates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 60 publications
(88 reference statements)
0
46
0
Order By: Relevance
“…Muscle strains in the lower extremity are the most common injuries in athletes. 1,5,7,8,9,13 The high incidence of hamstring strains has been reported in previous studies. 5,13 Hamstring strains are also recognized as a cause of disability in many sports.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Muscle strains in the lower extremity are the most common injuries in athletes. 1,5,7,8,9,13 The high incidence of hamstring strains has been reported in previous studies. 5,13 Hamstring strains are also recognized as a cause of disability in many sports.…”
Section: Discussionmentioning
confidence: 67%
“…1,5,7,8,9,13 The high incidence of hamstring strains has been reported in previous studies. 5,13 Hamstring strains are also recognized as a cause of disability in many sports. 1 Dick et al 6 reported that according to 16 years of data from the US NCAA Injury Surveillance Program, upper leg injuries accounted for 12% of all reported game time-loss injuries in collegiate baseball.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, it has been shown that high levels of finger strength can differentiate elite climbers from their nonelite counterparts. 31 Static trunk strength, upper limb strength, and power are moderately associated with elite 6 Specific hamstring exercises (eg, moderate-weight resistive bands, leg curl machines, and double-leg stiff leg lifting in a pain protected range of motion) [6][7][8][9] Begin regional upper-quadrant sports-specific muscle conditioning, including finger strengthening 10 Phase 2: Low velocity strengthening Low velocity concentric full range of motion hamstring-specific exercises with increasing resistive load using machines and free weights (eg, heavy elastic bands, knee curl machines, [6][7][8][9] and deadlifts 7 ) Phase 3: High load strengthening and functional reconditioning…”
Section: The Physiological Profilementioning
confidence: 99%
“…The injury burden varied from 116.3 to 157.1 missed matches due to injury per club per season and hamstring strains were the most common (mean incidence: 6 injuries per club per season) and burdensome injury (mean burden: 20 missed matches per club per season). 2 The risk of injuries in ARF appears to be increasing with a more recent report 4 indicating an overall injury incidence of 41.7 injuries per standardized club in the 2015 season. Additionally, hamstring injuries remain a substantial problem and were responsible for 19.1 missed games per club in the 2015 season.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, hamstring injuries remain a substantial problem and were responsible for 19.1 missed games per club in the 2015 season. 4 In an attempt to mitigate these high levels of injury in ARF, the Translating Research into Injury Prevention Practice (TRIPP) Model has been promoted as a methodological framework for injury prevention research. 5 In this model, identifying risk factors and mechanisms for common injuries has been promoted as an important focus of injury prevention research in populations where injury prevalence is known.…”
Section: Introductionmentioning
confidence: 99%